Postsecondary organizations and their role in advancing sustainable smart cities: towards a system-oriented perspective - Zambroni De Souza, Antonio Carlos; Alencar, Paulo; Cowan, Donald (Frontiers in Education, 2024)
Postsecondary institutions such as public and private universities have a key role to play in the development of sustainable smart cities. This paper discusses aspects of this role in terms of historical contributions, examples of contributions from the standpoint of two universities, and potential future contributions. The treatment of these aspects from a system-oriented perspective is also addressed. Researchers working on leading edge technologies have resources that enable them to introduce disruptive solutions that enhance the well being of society. On the other hand, it is clear that different university realities demand unique actions depending on whether they reside in developing or developed countries, although common social problems have also been identified. Overall, there is an opportunity for universities to test new ideas and implement them in communities, especially where they reside. We discuss the role of universities in a broad sense, where contributions are briefly described and acknowledged. The focus is on applications for sustainability and social good that have been or could be developed in universities as new research opportunities to improve the quality of life of the general population. We also argue that it is essential to consider university contributions to the creation of smart cities in the context of a system-oriented perspective.